The winner is agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Agriculture is returning to the main public agendas, it seems. The four winners of the Right Livelihood Awards for 2000 to be presented in Stockholm on 8 December include the Ethiopian scientist Tewolde Berhan Gebre Egziabher. The jury praised...